Denning Phenology Mediates Sea‐Ice Loss Impacts on Early Reproductive Success in Polar Bears - Marwan Naciri; Jon Aars; Marlène Gamelon; Magnus Andersen; Andrew E. Derocher; Øystein Wiig; Sarah Cubaynes (Global Change Biology, 2026)
Climate change is disrupting myriad biological processes, including the ability of species to synchronize life‐history events with optimal environmental conditions, with potential fitness impacts. Changes in migratory and breeding phenology and their consequences on fitness have been well studied in birds and some mammals. By contrast, changes in the phenology of overwinter sheltering and their influence on fitness have rarely been investigated. Pregnant female polar bears ( Ursus maritimus ) spend the winter fasting in a maternity den where they give birth and nurse their cubs until emergence in early spring. To sustain their fast, females rely on energy stores built primarily through consumption of ice‐associated seals. Here, we assess the impact of sea‐ice loss driven by climate change on early reproductive success acting through disrupted denning phenology and other unspecified factors. To do so, we develop a Bayesian hierarchical model combining capture–recapture and path modeling. We apply it to 38 years of capture–recapture data along with biologging data on denning status and phenology, while accounting for imperfect detection and uncertainty in individual denning schedules. We found that low sea‐ice availability led to earlier den emergence, which in turn reduced early litter survival and possibly litter size. By contrast, there was little evidence that sea‐ice availability affected early reproductive success through pathways independent of denning phenology (e.g., litter mass). Considering both direct and indirect effects, low sea‐ice availability reduced early litter survival but not the size of surviving litters. Given the strong link between sea‐ice conditions and body condition in female polar bears, we conclude that sea‐ice loss exerts an energetic constraint on denning females, forcing them to depart from dens early, which jeopardizes their cubs, ultimately reducing maternal fitness. Similar impacts of climate change may occur in other species where phenology is determined by body condition.

Per- and polyfluoroalkyl substances (PFAS) and miscarriage: The Norwegian Mother, Father and Child Cohort study - Thea Grindstad; Maria C. Magnus; Alessandro Di Nallo; Cecilia Høst Ramlau-Hansen; Zeyan Liew; Hans Ivar Hanevik; Line S. Haug; Gro D. Andersen; Tormod Rogne; Eleni Papadopoulou; Per Magnus; Siri E. Håberg; et al. (Environmental Research, 2026)

Boron sources of tourmaline-rich Nb-Y-F-pegmatites in south Norway: Implications for pegmatite melt origin - Erika De La Cruz; Axel Müller; Robert B. Trumbull; Pedro Faria; Tom Andersen; Muriel Erambert; Magnus Kristoffersen (Precambrian Research, 2024)

Changes in testing and incidence of Chlamydia trachomatis and Neisseria gonorrhoeae – the possible impact of the COVID-19 pandemic in the three Scandinavian countries - Lovisa Ivarsson; Magdalena de Arriba Sánchez de la Campa; Karin Elfving; Hong Yin; Karolina Gullsby; Lisa Stark; Berit Andersen; Steen Hoffmann; Åsa Gylfe; Magnus Unemo; Björn Herrmann (Infectious Diseases, 2022)

Freely chosen cadence during ergometer cycling is dependent on pedalling history - Ernst A. Hansen; Emma Nøddelund; Frederikke S. Nielsen; Mads P. Sørensen; Magnus Ø. Nielsen; Maria Johansen; Mathias H. Andersen; Morten D. Nielsen (European Journal of Applied Physiology, 2021)

Parametric Study of a Taut Compliant Mooring System for a FOWT Compared to a Catenary Mooring - Magnus Thorsen Bach-Gansmo; Stian Kielland Garvik; Jonas Bjerg Thomsen; Morten Thøtt Andersen (Journal of Marine Science and Engineering, 2020)
The catenary mooring system is a well recognized station keeping method. However, there could be economical and environmental benefits of reducing the footprint. In the last decades, more focus has been given to synthetic mooring lines and different mooring layouts to optimize the levelized cost of energy (LCOE) for offshore renevable energy converters such as wave energy converters. Therefore, this work presents a parametric study of two important parameters, namely the mooring line angle and line pretension, for a taut mooring configuration focusing on the dynamic response when applied to the TetraSpar floating foundation compared to a catenary mooring system. The work is based on experimental results conducted in the wave basin at Aalborg University (AAU) and compared to analytical stiffness calculations. In addition, a numerical model was tuned based on the main dynamics to achieve the tension response. The results showed satisfying dynamic behavior where the angle and pretension mainly influenced the surge and yaw natural periods. The motion response showed similar behavior between the chosen parameters, and larger pitch amplitudes were found compared to the catenary system.

External validation of the HANDOC score – high sensitivity to identify patients with non-beta-haemolytic streptococcal endocarditis - Torgny Sunnerhagen; Malene Højgaard Andersen; Niels Eske Bruun; Henning Bundgaard; Kasper Karmark Iversen; Magnus Rasmussen (Infectious Diseases, 2020)

Spatiotemporal variation in home range size of female polar bears and correlations with individual contaminant load - Floris M. van Beest; Jon Aars; Heli Routti; Elisabeth Lie; Magnus Andersen; Viola Pavlova; Christian Sonne; Jacob Nabe-Nielsen; Rune Dietz (Polar Biology, 2016)

Identifying Hot Spots of Agricultural Nitrogen Loss Within the Baltic Sea Drainage Basin - Hans Estrup Andersen; Gitte Blicher-Mathiesen; Hans Thodsen; Peter Mejlhede Andersen; Søren E. Larsen; Per Stålnacke; Christoph Humborg; Carl-Magnus Mörth; Erik Smedberg (Water, Air, & Soil Pollution, 2016)

Shifts in female polar bear (Ursus maritimus) habitat use in East Greenland - Kristin L. Laidre; Erik W. Born; Patrick Heagerty; Øystein Wiig; Harry Stern; Rune Dietz; Jon Aars; Magnus Andersen (Polar Biology, 2015)

Reduction of Baltic Sea Nutrient Inputs and Allocation of Abatement Costs Within the Baltic Sea Catchment - Fredrik Wulff; Christoph Humborg; Hans Estrup Andersen; Gitte Blicher-Mathiesen; Mikołaj Czajkowski; Katarina Elofsson; Anders Fonnesbech-Wulff; Berit Hasler; Bongghi Hong; Viesturs Jansons; Carl-Magnus Mörth; James C. R. Smart; et al. (Ambio, 2014)

Polar bear (Ursus maritimus) maternity den distribution in Svalbard, Norway - Magnus Andersen; Andrew E. Derocher; Øystein Wiig; Jon Aars (Polar Biology, 2012)

Linkage disequilibrium between the CYP2C19*17 allele and wildtype CYP2C8 and CYP2C9 alleles: identification of CYP2C haplotypes in healthy Nordic populations - Rasmus S. Pedersen; Charlotte Brasch-Andersen; Sarah C. Sim; Troels K. Bergmann; Jónrit Halling; Maria S. Petersen; Pál Weihe; Hege Edvardsen; Vessela N. Kristensen; Kim Brøsen; Magnus Ingelman-Sundberg (European Journal of Clinical Pharmacology, 2010)

Accuracy and precision in estimation of age of Norwegian Arctic polar bears (Ursus maritimus) using dental cementum layers from known-age individuals - Signe N. Christensen-Dalsgaard; Jon Aars; Magnus Andersen; Christina Lockyer; Nigel G. Yoccoz (Polar Biology, 2010)

Sexual dimorphism and the mating ecology of polar bears (Ursus maritimus) at Svalbard - Andrew E. Derocher; Magnus Andersen; Øystein Wiig; Jon Aars (Behavioral Ecology and Sociobiology, 2010)

Movements of two Svalbard polar bears recorded using geographical positioning system satellite transmitters - Magnus Andersen; Andrew E. Derocher; Øystein Wiig; Jon Aars (Polar Biology, 2008)

Short-term behavioural response of polar bears (Ursus maritimus) to snowmobile disturbance - Magnus Andersen; Jon Aars (Polar Biology, 2008)

Gender differences and determinants of aerobic fitness in children aged 8–11 years - Magnus Dencker; Ola Thorsson; Magnus K. Karlsson; Christian Lindén; Stig Eiberg; Per Wollmer; Lars Bo Andersen (European Journal of Applied Physiology, 2007)

Gender differences and determinants of aerobic fitness in children aged 8–11 years - Magnus Dencker; Ola Thorsson; Magnus K. Karlsson; Christian Lindén; Stig Eiberg; Per Wollmer; Lars Bo Andersen (European Journal of Applied Physiology, 2006)

ABUNDANCE OF RINGED SEALS ( PUSA HISPIDA ) IN THE FJORDS OF SPITSBERGEN, SVALBARD, DURING THE PEAK MOLTING PERIOD - Bjørn A. Krafft; Kit M. Kovacs; Magnus Andersen; Jon Aars; Christian Lydersen; Torbjørn Ergon; Tore Haug (Marine Mammal Science, 2006)
Ringed seal ( Pusa hispida ) abundance in Spitsbergen, Svalbard, was estimated during the peak molting period via aerial, digital photographic surveys. A total of 9,145 images, covering 41.7%–100% of the total fast‐ice cover (1,496 km 2 ) of 18 different fjords and bays, were inspected for the presence of ringed seals. A total of 1,708 seals were counted, and when accounting for ice areas that were not covered by images, a total of 3,254 (95% CI: 3,071–3,449) ringed seals were estimated to be hauled out during the surveys. Extensive behavioral data from radio‐tagged ringed seals (collected in a companion study) from one of the highest density fjords during the molting period were used to create a model that predicts the proportion of seals hauled out on any given date, time of day, and under various meteorological conditions. Applying this model to the count data from each fjord, we estimated that a total of 7,585 (95% CI: 6,332–9,085) ringed seals were present in the surveyed area during the peak molting period. Data on interannual variability in ringed seal abundance suggested higher numbers of seals in Van Keulenfjorden in 2002 compared to 2003, while other fjords with very stable ice cover showed no statistical differences. Poor ice conditions in general in 2002 probably resulted in seals from a wide area coming to Van Keulenfjorden (a large fjord with stable ice in 2002). The total estimated number of ringed seals present in the study area at the time of the survey must be regarded as a population index, or at least a minimum estimate for the area, because it does not account for individuals leaving and arriving, which might account for a considerable number of animals. The same situation is likely the case for many other studies reporting aerial census data for ringed seals. To achieve accurate estimates of population sizes from aerial surveys, more extensive knowledge of ringed seal behavior will be required.

Daily physical activity and its relation to aerobic fitness in children aged 8–11 years - Magnus Dencker; Ola Thorsson; Magnus K. Karlsson; Christian Lindén; Jesper Svensson; Per Wollmer; Lars Bo Andersen (European Journal of Applied Physiology, 2006)

Diet composition of polar bears in Svalbard and the western Barents Sea - Andrew E. Derocher; Øystein Wiig; Magnus Andersen (Polar Biology, 2002)

Studies on the sedimentation of influenza virus - S. Gard; P. Magnus; A. Svedmyr; A. Birch-Andersen (Archives of Virology, 1952)